Age and Sex-Related Changes in Retinal Function in the Vervet Monkey - Catarina Micaelo-Fernandes; Joseph Bouskila; Roberta M. Palmour; Jean-François Bouchard; Maurice Ptito (Cells, 2022)
Among the deficits in visual processing that accompany healthy aging, the earliest originate in the retina. Moreover, sex-related differences in retinal function have been increasingly recognized. To better understand the dynamics of the retinal aging trajectory, we used the light-adapted flicker electroretinogram (ERG) to functionally assess the state of the neuroretina in a large cohort of age- and sex-matched vervet monkeys (N = 35), aged 9 to 28 years old, with no signs of obvious ocular pathology. We primarily isolated the cone–bipolar axis by stimulating the retina with a standard intensity light flash (2.57 cd/s/m2) at eight different frequencies, ranging from 5 to 40 Hz. Sex-specific changes in the voltage and temporal characteristics of the flicker waveform were found in older individuals (21–28 years-old, N = 16), when compared to younger monkeys (9–20 years-old, N = 19), across all stimulus frequencies tested. Specifically, significantly prolonged implicit times were observed in older monkeys (p < 0.05), but a significant reduction of the amplitude of the response was only found in old male monkeys (p < 0.05). These changes might reflect ongoing degenerative processes targeting the retinal circuitry and the cone subsystem in particular. Altogether, our findings corroborate the existing literature in humans and other species, where aging detrimentally affects photopic retinal responses, and draw attention to the potential contribution of different hormonal environments.